Design of an Efficiency Power Load Control Device on Production Machines with SCADA Basen on Programmable Logic Controller and Smartphone - Supriyadi, Edy; Multi, Abdul; Ilyas, Iriandi; Jayanto Ramadhan, Anthony (International Journal of Advanced Multidisciplinary, 2024)
With limited electrical resources and the increasing use of loads on the industry, it is required to optimize the use of electrical power. Thus, it requires continuous monitoring and automatic load control. Overall monitoring of power loads, and electrical control settings in the optimization of production machines that can be monitored remotely and comprehensively. To overcome this problem, the design of the electrical power load control device on production machines with scada based on programmable logic controllers and smartphones is made. This study uses an experimental method to obtain a suitable machine simulator, then the following steps are carried out: collecting data and information, determining the controller and communication system, making hardware design, wiring simulator, software controller design, android smartphone software design and HMI software design. As for the control of the electric power control system in optimizing the operation of production machines with scada and smartphones. From the test results obtained a system that can work well. This is evidenced by looking at the measurement data for testing the input/output signal from the controller by looking directly at the controller, as well as on the HMI monitor by displaying the amount of electrical power used and the amount of available electrical resources, which is done by simulating analog input/output. with a scale of 0-100% (0-10 V), 0-1000 KW (0-10 V).